2015
DOI: 10.1037/adb0000106
|View full text |Cite
|
Sign up to set email alerts
|

Parental involvement in brief interventions for adolescent marijuana use.

Abstract: Adolescents (aged 12–18 years) identified in a school setting as abusing marijuana and other drugs were randomly assigned to complete one of two brief interventions (BIs). Adolescents and their parent (N = 259) were randomly assigned to receive either a 2-session adolescent only (BI-A) or a 2-session adolescent and additional parent session (BI-AP). Interventions were manualized and delivered in a school setting by trained counselors. Adolescents were assessed at intake and at 6 months following the completion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
1
12
0
3
Order By: Relevance
“…A recent study found significant improvements in cannabis use reductions when assessing the efficacy of adding a session based on the family therapy approach with a focus on parental monitoring to a two session MET intervention over six months, however; this difference was no longer significant at 12 month follow-up (127,128). Secondary analysis of these results found that parental involvement was more effective for adolescents with cannabis dependence but without a conduct disorder and less effective for those with such disorder (129). Finally, reductions to cannabis use frequency were significant at twelve weeks following a four-session MET intervention with (n=68) or without abstinence-based CM adjunct (n=68) with no between group differences (124).…”
Section: Met For Adolescentsmentioning
confidence: 98%
“…A recent study found significant improvements in cannabis use reductions when assessing the efficacy of adding a session based on the family therapy approach with a focus on parental monitoring to a two session MET intervention over six months, however; this difference was no longer significant at 12 month follow-up (127,128). Secondary analysis of these results found that parental involvement was more effective for adolescents with cannabis dependence but without a conduct disorder and less effective for those with such disorder (129). Finally, reductions to cannabis use frequency were significant at twelve weeks following a four-session MET intervention with (n=68) or without abstinence-based CM adjunct (n=68) with no between group differences (124).…”
Section: Met For Adolescentsmentioning
confidence: 98%
“…BIs following screening procedures are promising approaches for addressing substance use and associated risks that aim to increase motivation to change behaviour for adolescents who do not meet diagnostic criteria for a substance use disorder (Carney, Myers, Louw, & Okwundu, 2016) but more evidence is needed with this population (Bazzi & Saitz, 2018) to ensure the efficacy of such interventions. Previous studies have found that incorporating a caregiver (e.g., parent) component within BIs have led to significantly better substance use and other behavioural outcomes for adolescents compared to BIs that focus on the adolescent only (Piehler & Winters, 2015;Winters, Lee, Botzet, Fahnhorst, & Nicholson, 2014). This is not surprising given evidence that parenting style is a significant predictor of adolescent substance use (Brook, Morojele, Pahl, & Brook, 2006;Reddy et al, 2013) and findings that parents can protect adolescents against substance use if they control, monitor and set limits on their children's behaviour (Groenewald & Bhana, 2016).…”
mentioning
confidence: 99%
“…Abar, 2012;Mares et al, 2012;Napper et al, 2015Napper et al, , 2016Wood et al, 2004). For this reason, a number of cannabis interventions for adolescents and emerging adults have involved parents (Grossbard et al, 2010), but with only mixed success (Dennis et al, 2004;Piehler & Winters, 2015;Smeerdijk et al, 2012;Stanger et al, 2015;Winters et al, 2014). A clearer understanding of parental influences on CU may help to bolster intervention efficacy.…”
Section: Introductionmentioning
confidence: 99%